Development of an indoor guidance system for unmanned aerial vehicles with power industry applications. Issue 1 (1st January 2017) - Wu, Kevin J.; Gregory, Thomas Stan; Moore, Julian; Hooper, Bryan; Lewis, Dexter; Tse, Zion Tsz Ho
Abstract : Unmanned aerial vehicle (UAV) systems are experiencing a period of rapid growth as potential for industrial and commercial applications are arising. Conventional UAV technologies focus on outdoor large area navigation, utilising global positioning system, which has proven to be less effective in enclosed environments. The authors aim to develop an indoor navigation system, specifically for industrial applications which require custom sensing technologies to aid in pilot navigation. A custom sensing array, featuring ultrasonic transceivers, was developed to localise drone position in an enclosed known environment and provide pilot feedback. Six subjects were recruited to pilot the drone with and without the navigation system in an enclosed room to a pre‐set target at a known location in two cases: (i) with a line of sight, and (ii) without line of sight. Flight duration, number of collisions, and distance from target were recorded and used to quantify performance. Using the navigation system, subjects were able to reduce their flight duration on average by 19.7% during an obstructed line of sight, illustrating the increased ability and confidence in piloting the drone using the navigation system. This study serves to prove the potential of this device as an essential tool for indoor drone localisation and commercial inspections.